BRAILLE AND DIGITAL AUDIO-SUPPORTED READING TECHNIQUES AND ACHIEVEMENT IN ENGLISH LANGUAGE COMPREHENSION AMONG STUDENTS WITH VISUAL IMPAIRMENT IN IMO STATE, NIGERIA (2023)
Students with Visual Impairment (SVI) experience difficulties with sight-related activities and this hinders them from acquiring functional life skills like reading, which are important for success in academics and life in general. Reports have shown that many SVI in Imo State exhibit low achievement in English language comprehension. Previous studies have focused largely on provision, and the use of assistive technology as well as mobility training for SVI with little emphasis on interventions using braille and digital audio supported reading techniques for improving their reading comprehension skills. This study, therefore, was designed to determine the effects of Braille Reading (BR) and Digital Audio-supported Reading (DAsR) techniques on achievement in English language comprehension among SVI in Imo State, Nigeria. The moderating effects of onset of visual impairment and Emotional Intelligence (EI) were also examined. The study was anchored to Lev Vygotsky's Socio-cultural Theory, while a pretest-posttest, control group quasi-experimental design with a 3x2x2 factorial matrix was adopted. Three integrated public secondary schools (Boys’ Secondary School, Aboh, BSA; Girls’ Secondary School, Orlu, GSO; and Government Secondary School, Owerri, GSSO), were purposively selected. A screening conducted using the Snellen Chart revealed that there were only 17 SVI in the three integrated schools. All the 17 SVI were enumerated across the schools: BSA (8), GSO (5) and GSSO (4). The schools were randomly assigned to BR (8), DAsR (5) and control (4) groups. The instruments used were Bar-On Emotional Quotient Inventory (r=0.78), Achievement in English Language Comprehension Test (r=0.79) and instructional guides. The treatment lasted eight weeks. Data were analyzed using descriptive statistics, Analysis of covariance and Scheffe post-hoc test at 0.05 level of significance. The participants’ age was 16.35 ± 1.12 years, while 59.0% acquired visual impairment after birth. There was a significant main effect of treatment on achievement in English language comprehension among the participants (F (1.7) =3.21, partial = 0.39). Participants exposed to BR had the highest post mean achievement score in English language comprehension (53.06), followed by those in DAsR (45.34) and control (39.16) groups. Onset of visual impairment had no significant main effect on achievement in English language comprehension of the participants. The EI had no significant main effect on the achievement in English language comprehension of the participants. Treatment and onset of visual impairment had significant interaction effect on the achievement in English language comprehension of the participants (F (1,7) = 3.41, partial = 0.17). The two-way and three-way interaction effects of treatment and onset of visual impairment, treatment and EI, treatment, onset of visual impairment and EI, respectively were not significant on achievement in English language comprehension of the participants. Braille reading more than Digital audio-supported reading enhanced achievement in English language comprehension among students with visual impairment in Imo State, Nigeria. Special Educators should use both reading techniques in teaching students with visual impairment to enhance their achievement in English language comprehension.